Conflict, Social Capital and Managing Natural Resources : a West African Case Study. - Moore, K. M. (CAB International, 2004)
This book is the product of a research programme into sustainable agriculture and natural resource management. It focuses on the transition from agricultural and pastoral systems of arid and semi-arid regions of West Africa to more intensified agricultural and animal husbandry systems. Both technological options and decision tools are analysed, and a replicable methodology for building social capital within a rural community in the Inland Delta of the Niger River is presented. Fundamentally, this text presents a solid point of reference for a case study based on a research based development pr.